How the availability and adequacy of social support affect the general mental health of Swedish police officers - Hansson, Jonas; Padyab, Mojgan (Frontiers in Psychology, 2023)
Police work is stressful. A protective function against work stress and harm to mental health is social support, either within or outside work. This cross-sectional study analyzes the associations of quantitative (availability) and qualitative (adequacy) aspects of social support with general mental health among Swedish police officers. A total of 728 officers responded to a national survey. Bivariate analyses (t-test and chi square) identified continuous and categorical variables (respectively) statistically significantly associated with sex and social support. Pearson correlation coefficient was provided to indicate the associations between general mental health and different types of social support. Sex-stratified logistic regression modeling calculated crude and adjusted odds ratios (OR) with 95% confidence intervals (CI) and assessed the relationships between different types of social support, sociodemographic variables and general mental health. The findings show that low adequacy of attachment is associated with poorer mental health among female officers, although female officers also reported higher availability of both social interaction and attachment compared to male officers. We found an association between low work-related social support and poorer mental health among single male police officers. Moreover, police officers who worked shifts, were younger, had less work experience, and/or had no children reported higher availability of attachment, whereas older police officers reported higher adequacy of social interaction compared to younger police officers. Variation in the quantity and quality of close social relationships seems to be important to mental health. Police organizations need to be aware of this in their efforts to make the work environment more supportive. Social support might create an environment where officers feel more comfortable discussing their mental health concerns and seeking assistance.